If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -2) = 2 + -2x Reorder the terms: 9(-2 + x) = 2 + -2x (-2 * 9 + x * 9) = 2 + -2x (-18 + 9x) = 2 + -2x Solving -18 + 9x = 2 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -18 + 9x + 2x = 2 + -2x + 2x Combine like terms: 9x + 2x = 11x -18 + 11x = 2 + -2x + 2x Combine like terms: -2x + 2x = 0 -18 + 11x = 2 + 0 -18 + 11x = 2 Add '18' to each side of the equation. -18 + 18 + 11x = 2 + 18 Combine like terms: -18 + 18 = 0 0 + 11x = 2 + 18 11x = 2 + 18 Combine like terms: 2 + 18 = 20 11x = 20 Divide each side by '11'. x = 1.818181818 Simplifying x = 1.818181818
| 2u=2.2 | | 104=-8(m-5) | | 805=40(20+(-.4y))+15y | | C/3/=12 | | s+11=-5.4 | | 3x+63+x+21=180 | | 7x-10x+5x=5 | | 17x-4-13x=2(2x-3)+2 | | 2u=6.12 | | 3n-40-2n=15 | | s/-22=-17 | | 292+w=805 | | 4x+166=7x+196 | | 4x^2+15x+29=9x+2 | | -2(3x+8)=10 | | w/4-1=8-w/2 | | 10(x-7)=10x-70 | | X+70+52=180 | | 10(x+7)=10(x+10) | | 2x+3x+(-5)=-15 | | g+61=206 | | 7x+15-9x=19-13x+11x-4 | | 13x+23=180 | | f/-22=30 | | 3(5-7x)-4=-4(4x+1) | | 3x+12=3x-20 | | (15x^2)+24x+9=0 | | -20h=-860 | | iz+2conj(z)=6-i | | (40*x)+(15*y)=805 | | log(5598)=7x | | (x-8)/44=5 |